Barriers to broadband market development in rural areas in South Africa. - Macharia, Caroline Wangari (My University, 2013)
This research study investigates challenges affecting the supply and demand side factors of the broadband ecosystem that hinder the market development of broadband in rural areas in South Africa and how policy and regulation has affected the evolution of the broadband ecosystem in rural areas. Although the elements of the broadband ecosystem are strong and well placed in urban areas, not all elements of the broadband ecosystem in rural areas are in place and equally strong. The relative strengths and weaknesses of the different elements of the broadband ecosystem in rural areas are unknown and demand and supply side factors are not understood. Hence the broadband policy may not be based on a full understanding of the complex ecosystem. The study points to a classic case of market failure that exists in rural areas in relation to the broadband market development. The study identifies that a governance framework, investment management framework, universal access funding model, sufficient frequency spectrum resources, policies and regulation that specifically address the development of the broadband market in rural areas are lacking. Although the barriers and gaps identified in this study are known to the industry this research study goes further to corroborate from an academic research perspective the existence of these barriers that are affecting the broadband market development of rural areas.
Thesis (M.M. (ICT Policy and Regulation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development, 2013.
Keywords: Broadband; Rural areas; South Africa; Market development